STUDI EFISIENSI SALURAN SEKUNDER JARINGAN IRIGASI WUNDULAKO, KOLAKA - Fathur Rahman Rustan; Isramyano Yatjong; Mursalim Ninoy La Ola; Devia Eka Rachmawati (Universitas Sulawesi Barat, 2023)
Secondary Channel Efficiency Study Wundulako Irrigation Network, Kolaka. One of the government's efforts to prosper the community during the current COVID-19 pandemic is to ensure that the food security of the community can be met. To achieve this, the rice field area as a food barn for rice plants requires sufficient availability. In addition, the availability of water must be supported by good irrigation facilities and infrastructure. The efficiency of irrigation canals can be used as an indicator of the performance of an irrigation service area. The most common problem faced by many network operating systems is the low efficiency of air distribution. D. I. Wundulako is one of the irrigation areas that has the widest potential for rice fields in Kolaka Regency. However, until now, it can only flow 1,695 Ha out of a total area of ​​3,113 Ha. Along with the development conditions in the district, D. I. Wundulako has greatly affected air conditions, irrigation networks, building conditions and rice fields, and there has been a lot of water loss/leakage before reaching its final destination. This loss causes unfulfilled water needs in rice fields and plants in Wundulako irrigation, so it is necessary to conduct a study related to canals in the operation of Wundulako irrigation networks.